Early diagnosis of Ischemia Stroke using neural network - Anita, Thakur; Surekha, Bhanot; Mishra, S.N. (Universiti Malaysia Perlis, 2009)
Organized by School of Mechatronic Engineering (UniMAP) & co-organized by The Institution of Engineering Malaysia (IEM), 11th - 13th October 2009 at Batu Feringhi, Penang, Malaysia.